Diversity of Plant Species Along the Trail of the Botanical Forest Park (Tahura), North Sumatra - Nasrianti Syam; Nasution, Barita Raja; Siregar, Mawaddah Putri Arisma (JURNAL BIOLOGICA SAMUDRA, 2025)
This study was conducted to document and to describe the diversity of plant species along the trail of the Botanical Forest Park (Tahura) in North of Sumatra. The research employed an exploratory survey method using a transect approach, with species identification based on observable morphological characteristics in the field. Observations recorded a total of 114 plant species categorized as cultivated or agricultural plants, predominantly found in areas near settlements. In contrast, within zones of natural vegetation, 106 plant species were identified, distributed across 48 different families. These findings reflect a high level of floral diversity in Tahura Medan area, encompassing both native vegetation and cultivated species. Such biodiversity is not only essential for supporting environmental conservation efforts but also holds strategic value as a resource for tropical ecology education, particularly within urban settings.